2006
DOI: 10.1007/s00122-006-0322-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome balance in six successive generations of the allotetraploid Festuca pratensis × Lolium perenne

Abstract: In the allotetraploid, Festuca pratensis Huds. (2n = 4x = 28) x Lolium perenne L. (2n = 4x = 28) the balance of chromatin, as determined by GISH, changes over successive generations of open pollination in favour of L. perenne. There is extensive recombination between chromosomes of the two parental genomes, as well as substitution of whole Festuca chromosomes by whole Lolium chromosomes. The total number of Lolium chromosomes increased from a mean 14.36 in the F(2) to 16.26 in the F(6), and the total number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 27 publications
9
59
1
Order By: Relevance
“…Canter et al (1999) measured the total lengths of Lolium and Festuca chromatin in festulolium, and found that Lolium chromatin was longer than Festuca chromatin. Dominance of the Lolium genome in festulolium was also reported by Kopecky et al (2005), and Zwierzykowski et al (2006) observed a reduction in the number of Festuca chromosomes in advanced generations of F. pratensis (4x) × L. multiflorum (4x) hybrids. Henikoff et al (2001) proposed that both the centromere-specific histone H3 (CENH3) and centromeric DNA evolve rapidly, and that the interaction between CENH3 and centromeric DNA plays an important role in maintaining stable inheritance in eukaryotes; i.e., differences in centromere evolution create species barriers.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Canter et al (1999) measured the total lengths of Lolium and Festuca chromatin in festulolium, and found that Lolium chromatin was longer than Festuca chromatin. Dominance of the Lolium genome in festulolium was also reported by Kopecky et al (2005), and Zwierzykowski et al (2006) observed a reduction in the number of Festuca chromosomes in advanced generations of F. pratensis (4x) × L. multiflorum (4x) hybrids. Henikoff et al (2001) proposed that both the centromere-specific histone H3 (CENH3) and centromeric DNA evolve rapidly, and that the interaction between CENH3 and centromeric DNA plays an important role in maintaining stable inheritance in eukaryotes; i.e., differences in centromere evolution create species barriers.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies examining the ratio of genomic composition in festulolium measured the length of chromatin in each genus using projectors or on a computer screen (Canter et al 1999, Zwierzykowski et al 2006. However, image analysis software simplifies quantitative evaluations of visual information and costs considerably less than previous methods.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrate the stress tolerance present in the fescues, but also the importance of the adaptational level of winter survival in perennial ryegrass as compared with Italian ryegrass. However, with the amphiploid approach a genetic drift is clear and investigations have revealed significant and progressive loss of fescue chromosomes throughout generations (Zwierzykowski et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lolium species are high yielding and have good forage quality while the Festuca species are more persistent under stress conditions (Thomas & Humphreys 1991). Fertile hybrids between tetraploid F. pratensis and both tetraploid L. perenne and tetraploid L. multiflorum (Festulolium) have been developed in europe and the United states (Zwierzykowski et al 2006). Although genetic exchange occurs freely between Festuca and Lolium chromosomes, there is a tendency for Lolium chromatin to progressively dominate over successive generations.…”
Section: Awareness and Use Of Secondary Gene-poolsmentioning
confidence: 99%